2014
DOI: 10.1208/s12249-014-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Targeted Delivery of Docetaxel by Glutathione-Coated Nanoparticles for Brain Cancer

Abstract: Gliomas are some of the most aggressive types of cancers but the blood-brain barrier acts as an obstacle to therapeutic intervention in brain-related diseases. The blood-brain barrier blocks the permeation of potentially toxic compounds into neural tissue through the interactions of brain endothelial cells with glial cells (astrocytes and pericytes) which induce the formation of tight junctions in endothelial cells lining the blood capillaries. In the present study, we characterize a glutathione-coated docetax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…GSH receptors at the BBB interface offer an option in targeting these receptors by GSH-coated nanoparticles to escalate the active or passive transcytosis of therapeutic agents to the brain [12,13]. GSH-PEGylated liposomes have been effectively applied as a brain drug delivery platform for the improvement of numerous treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH receptors at the BBB interface offer an option in targeting these receptors by GSH-coated nanoparticles to escalate the active or passive transcytosis of therapeutic agents to the brain [12,13]. GSH-PEGylated liposomes have been effectively applied as a brain drug delivery platform for the improvement of numerous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…GSH, an endogenous tripeptide, possesses a central nervous system (CNS) concentration up to 3 mM [12]. It has antioxidant-like characteristics and is readily transported across the BBB [13].…”
Section: Introductionmentioning
confidence: 99%
“…In‐Vitro BBB Permeation Model : A Transwell model was established to investigate the BBB permeability of the H–S–R NPs1, which was adapted from a previously reported method . Briefly, Transwell permeable supports with 0.4‐μm porous membranes (Corning Inc., NY, USA) were purchased and coated with rat tail collagen I (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Since there are many kinds of receptors expressed on the endothelial BBB, different studies attempted to exploit some of them to facilitate the transport of NPs. Among the most common receptors extensively studied are the glucose transporter GLUT 99-102 , transferrin receptor 33,102-105 , LDL receptor 106,107 and glutathione transporters[108][109][110] . It was also shown that dual targeting can improve the BBB passage by adding two targeting moieties: one that first target the BBB and then target specifically the glioma cells99,102,106 .…”
mentioning
confidence: 99%